2010
DOI: 10.1021/bm1001476
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Fabrication of Fast-Degradable, Water-Soluble Polycarbonate Functionalized with Tertiary Amine Groups in Backbone

Abstract: Degradable polymers with specifically designed functionality have wide applications in biomedical fields. We reported herein the synthesis and characterization of a water-soluble and fast-degradable polycarbonate, functionalized with tertiary amine groups in the backbone. A novel cyclic carbonate monomer, namely, 6,14-dimethyl-1,3,9,11-tetraoxa-6,14-diaza-cyclohexadecane-2,10-dione (ADMC)(2), was synthesized and polymerized to provide the title polycarbonate [poly(ADMC)] via Novozym-435 lipase or tin(II) 2-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Feng et al showed that linear polycarbonates functionalized with tertiary amines could degrade in three months without creating any significant toxicity upon degradation but without antimicrobial properties. 38 The goal of this study is to design an ideal hydrogel material for wound healing applications, featuring a combination of antimicrobial properties and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al showed that linear polycarbonates functionalized with tertiary amines could degrade in three months without creating any significant toxicity upon degradation but without antimicrobial properties. 38 The goal of this study is to design an ideal hydrogel material for wound healing applications, featuring a combination of antimicrobial properties and biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polymer may result in aseptic inflammation from the acid degradation products. Hydroxypatite (HAP) possesses chemical composition and crystal structure similar to that of human bone [3,4] and excellent biocompatibility, bioactivity and bone conduction capacity. So HAP is an ideal biomimetic bone tissue engineering material [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic polycarbonates (APCs), represented by poly(trimethylene carbonate) (PTMC), are one important kind of biodegradable polymers and commonly prepared by ring‐opening polymerization (ROP) . APCs can degrade with relatively slower rate and have weak inflammatory effect of degradation compounds, which is a marked advantage over polyester and particularly attractive to sustained drug delivery application.…”
Section: Introductionmentioning
confidence: 99%